2023
DOI: 10.3390/ijerph20032407
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, Resilience, Supervisory Support, and Quitting Intention among Healthcare Professionals in Saudi Arabia: A National Cross-Sectional Survey

Abstract: Although personal resilience and supervisory support are known to reduce the impact of burnout and quitting intention, there is limited data available to explore these relationships among healthcare professionals (HCPs) in Saudi Arabia. This study aimed to assess the prevalence of burnout and explore its association with resilience, supervisory support, and intention to quit among Saudi Arabian HCPs. Methods: A cross-sectional survey was distributed to a convenience sample of HCPs between April and November 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…Third, organizational support and resilience, resource factors from job and personal domain respectively, both negatively affected burnout. Similarly, a study of healthcare professionals in Saudi Arabia found a significant negative association between resilience and burnout [ 74 ]. Healthcare professionals with higher levels of resilience had lower levels of burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Third, organizational support and resilience, resource factors from job and personal domain respectively, both negatively affected burnout. Similarly, a study of healthcare professionals in Saudi Arabia found a significant negative association between resilience and burnout [ 74 ]. Healthcare professionals with higher levels of resilience had lower levels of burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Jam kerja yang diperpanjang, dan kerja shift yang sering berubah adalah tuntutan pekerjaan yang pada akhirnya berkontribusi pada peningkatan resiko kelelahan emosional (Siraj et al, 2023). Kelahan emosional mengacu pada perasaan emosional yang berlebihan dan terkuras oleh kontak seseorang dengan orang lain (Wallace & Coughlan, 2023).…”
Section: Latar Belakangunclassified
“…Although burnout has been continuously reported among medical professionals (Siraj et al, 2023), current evidence shows that students pursuing medical careers, such as medical and dental (Bahlaq et al, 2023) and respiratory therapy students (Siraj et al, 2022) are also at increased risk of burnout.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Although burnout has been continuously reported among medical professionals ( Siraj et al, 2023 ), current evidence shows that students pursuing medical careers, such as medical and dental ( Bahlaq et al, 2023 ) and respiratory therapy students ( Siraj et al, 2022 ) are also at increased risk of burnout. Similarly, a study conducted in Belgium on 2,275 nursing and midwifery students revealed that 50% of the participants endured high levels of burnout ( Baudewyns et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%